Training response of adolescent Kenyan town and village boys to endurance running - Larsen, H. B.; Nolan, T.; Borch, Ch.; Soendergaard, H. (Scandinavian Journal of Medicine & Science in Sports, 2005)
To investigate the response to endurance training on physiological characteristics, 10 Nandi town boys and 14 Nandi village boys 16.5 and 16.6 years of age, respectively, from western Kenya performed 12 weeks of running training. The study was performed at altitude (2000 m.a.s.l. 595 mm Hg). Training heart rate and speed were registered during every training session throughout the entire training period. While town and village boys trained at similar heart rates (172.1 vs. 172.5 beats min1), the training speed of the town boys was 9% lower compared with the village boys (12.4 vs. 13.6 km h1, P<0.001). Significant increases in VO2max were observed in the town boys (from 50.3 to 55.6 mL kg1 min1, P<0.001) and in village boys (from 56.0 to 59.1 mL kg1 min1, P<0.002). Significant decreases in submaximal heart rate (from 172.4 to 160.3 beats min1 (P<0.005)), blood lactate (from 2.7 to 1.4 mmol L1 (P<0.005)) and ammonia concentration (from 102.0 to 71.4 mol L1 (P<0.01)) at 9.9 km h1 were observed in the town boys, while similar decreases in heart rate (from 170.2 to 159.2 beats min1 (P<0.001)), blood lactate (from 2.4 to 1.4 mmol L1 (P<0.001)) and ammonia concentration (from 102.5 to 72.7 lmol L1 (P<0.001)) at 10.9 km h1 were observed in the village boys. The oxygen cost of running was decreased from 221.5 to 211.5 mL kg1 km1 (P<0.03) in the town boys and from 220.1 to 207.2 mL kg1 km1 (P<0.01) in the village boys. The 5000 m performance time of the town boys was significantly greater than that of the village boys (20.25 vs. 18.42 min (P=0.01)). It is concluded that no difference was observed in trainability with respect to VO2max, running economy, submaximal heart rate, and submaximal blood lactate and ammonia concentration between Kenyan Nandi town and village boys. The higher performance level of the village boys was likely due to a higher VO2max of these boys.